A tale of two communication tools: Discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2017)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.

A tale of two communication tools: Discussion-forum and mobile instant-messaging apps in collaborative learning - Sun, Zhong; Lin, Chin-Hsi; Wu, Minhua; Zhou, Jianshe; Luo, Liming (British Journal of Educational Technology, 2017)
Computer-supported collaborative learning (CSCL) has shown considerable promise, but thus far the literature has tended to focus on individual technological tools, without due regard for how the choice of one such tool over another impacts CSCL, either in outline or in detail. The present study, therefore, directly compared the learning-related uses of an online discussion forum against such use of a mobile instant-messaging app by the same group of 78 upper-division undergraduate pre-service teachers in China. The participants were asked to use one of the two communication tools during the first of three learning activities, then to switch to the other during the second, and to choose their preferred tool for the third. Based on the results of content analysis, social-network analysis and a survey of the students' attitudes, it was found that while both tools facilitated collaborative learning, they appeared to have different affordances. Specifically, using the online discussion forum resulted in more communication aimed at knowledge construction, while using the mobile instant-messaging app resulted in more social interactions.

A Quasi-Experimental Study of the Classroom Practices of English Language Teachers and the English Language Proficiency of Students, in Primary and Secondary Schools in Bangladesh - Power, Tom; McCormick, Robert; Asbeek-Brusse, Elsbeth (2017)
English in Action (EIA) is an English language teacher development project based in Bangladesh that was intended to run from 2008 to 2017, but which was extended at the request of the Government of Bangladesh, with additional funding from UKAID, for a further year to 2018. By the time of the design of this study (2014-2015) EIA was drawing to the end of upscaling (phase III, 2011-2014) and entering institutionalisation and sustainability (phase IV, 2014-17, extended 2018). Successive prior studies had indicated substantial success in improving both teachers’ classroom practices and student learning outcomes, over the pre-project baseline (e.g. EIA 2011, 2012). The 2014 Annual Review of EIA recommended that in the final phase, EIA should explore whether it would be possible to carry out a study that compared a ‘counterfactual’ or control-group of teachers and students, to the ‘EIA’ or treatment schools: i.e. a Randomised Control Trial or Quasi-Experimental study. A proposal for a Quasi-Experimental study was developed in collaboration with DFID’s South Asia Research Hub (SARH), which also provided the additional funding necessary to implement such a study. The teachers and students who were the subject of this study, were the fourth cohort to participate in English in Action (together with teachers from ‘control’ schools, in the same Upazilas). This fourth EIA cohort included Schools, Teachers and Students from approximately 200 Upazilas (of approximately 500 in total) across Bangladesh, including some of the most disadvantaged areas (with reference to UNICEF deprivation index), such as Char, Hoar and Monga districts. Teachers took part in a school-based teacher development Programme, learning communicative language teaching approaches through carrying out new classroom activities, guided by teacher development videos that showed teachers, students and schools similar to those across the country. Teachers also had classroom audio resources for use with students. All digital materials were available offline, on teachers own mobile phones, so there is no dilution of the Programmes core messages about teaching and learning, by some intermediary coming between the teacher and the materials. Teachers were supported through these activities, by other teachers in their schools, by their head teachers and by local education officers. Some teachers from each area were also given additional support and guidance from divisional EIA staff, to act as Teacher Facilitators, helping teachers work through activities and share their experiences at local cluster meetings. Whereas previous cohorts of teachers had attended eight local teacher development meetings over their participation in the project, for Cohort Four, this was reduced to four meetings, with a greater emphasis being placed on support in school by head teachers, as well as support from local education officers. This change was part of the move towards institutionalisation and sustainability of project activities within and through government systems and local officers. The purpose of this study was both to provide the evaluation evidence required for the final phase of the EIA project and to contribute to the international body of research evidence on effective practices in teacher development in low-to-middle income country contexts.